Unconditional Basic Income in the Framework of the Fourth Industrial Revolution: An Assessment for Turkey - (:unkn) unknown (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2020)
The main purpose of this article is to evaluate the arguments about the unconditional basic income (UBI), which is considered as a partial solution to alleviate poverty and reduce income inequalities. The study will first explore if there is a relationship between income inequality and neoliberalism, which is the dominant economic understanding. Second, it will examine if there is a relationship between an increase in unemployment rates in some countries like Turkey and the deepening of the 4th Industrial Revolution (4th IR). Third, it will seek an answer if it is possible to implement policies that will not leave anyone hungry and vulnerable in a capitalist economic system. Fourth, the paper will briefly evaluate some basic income experiments from Brazil, India, the US, Canada, and Finland to find satisfactory answers to the above questions. Next, the budgetary costs of three alternative UBI possibilities for Turkey are calculated. Finally, the article will make a modest theoretical contribution to increasing the likelihood of positive externality spread to society.
Keywords: Unconditional Basic Income; Poverty; Fourth Industrial Revolution; Positive Externalities; Turkey; POVERTY